Attacins: A Promising Class of Insect Antimicrobial Peptides - Francesco Buonocore; Anna Maria Fausto; Giulia Della Pelle; Tomislav Roncevic; Marco Gerdol; Simona Picchietti (MDPI AG, 2021)
Insects produce a large repertoire of antimicrobial peptides (AMPs) as the first line of defense against bacteria, viruses, fungi or parasites. These peptides are produced from a large precursor that contains a signal domain, which is cleaved in vivo to produce the mature protein with antimicrobial activity. At present, AMPs from insects include several families which can be classified as cecropins, ponericins, defensins, lebocins, drosocin, Metchnikowin, gloverins, diptericins and attacins according to their structure and/or function. This short review is focused on attacins, a class of glycine-rich peptides/proteins that have been first discovered in the cecropia moth (Hyalophora cecropia). They are a rather heterogeneous group of immunity-related proteins that exhibit an antimicrobial effect mainly against Gram-negative bacteria. Here, we discuss different attacin and attacin-like AMPs that have been discovered so far and analyze their structure and phylogeny. Special focus is given to the physiological importance and mechanism of action of attacins against microbial pathogens together with their potential pharmacological applications, emphasizing their roles as antimicrobials.